Experimental observation of carousel‐like phason flips in the decagonal quasicrystal Al60Cr20Fe10Si10. Issue 5 (13th August 2021) - He, Zhanbing; Maurice, Jean-Luc; Ma, Haikun; Wang, Yanguo; Li, Hua; Zhang, Tiantian; Ma, Xiuliang; Steurer, Walter
Abstract : Carousel‐like successive flippings of groups of atoms inside the decagonal clusters of decagonal quasicrystals were observed experimentally. The observed directionally successive phason flips occur mainly clockwise and occasionally anticlockwise. Abstract : Quasicrystals have special crystal structures with long‐range order, but without translational symmetry. Unexpectedly, carousel‐like successive flippings of groups of atoms inside the ∼2 nm decagonal structural subunits of the decagonal quasicrystal Al60 Cr20 Fe10 Si10 were directly observed using in situ high‐temperature high‐resolution transmission electron microscopy imaging. The observed directionally successive phason flips occur mainly clockwise and occasionally anticlockwise. The origin of these directional phason flips is analyzed and discussed.